The Extract of Corydalis yanhusuo Prevents Morphine Tolerance and Dependence - Lamees Alhassen; Khawla Nuseir; Allyssa Ha; Warren Phan; Ilias Marmouzi; Shalini Shah; Olivier Civelli (MDPI AG, 2021)
The opioid epidemic was triggered by an overprescription of opioid analgesics. In the treatment of chronic pain, repeated opioid administrations are required which ultimately lead to tolerance, physical dependence, and addiction. A possible way to overcome this conundrum consists of a co-medication that maintains the analgesic benefits of opioids while preventing their adverse liabilities. YHS, the extract of the plant Corydalis yanhusuo, has been used as analgesic in traditional Chinese medicine for centuries. More recently, it has been shown to promote analgesia in animal models of acute, inflammatory, and neuropathic pain. It acts, at least in part, by inhibiting the dopamine D2 receptor, suggesting that it may be advantageous to manage addiction. We first show that, in animals, YHS can increase the efficacy of morphine antinociceptive and, as such, decrease the need of the opioid. We then show that YHS, when coadministered with morphine, inhibits morphine tolerance, dependence, and addiction. Finally, we show that, in animals treated for several days with morphine, YHS can reverse morphine dependence and addiction. Together, these data indicate that YHS may be useful as a co-medication in morphine therapies to limit adverse morphine effects. Because YHS is readily available and safe, it may have an immediate positive impact to curb the opioid epidemic.